VD_FINDINFO 116/2010/PMR vom 6. September 2010 - VD Tribunal cantonal (2010)
MESURE PROVISIONNELLE, EXÉCUTION ANTICIPÉE, CONCURRENCE DÉLOYALE, PROHIBITION DE CONCURRENCE, CLIENTÈLE | 340b CO, 101 CPC, 109 al. 1 CPC, 92 al. 1 CPC, 14 LCD, 2 LCD